KORELASI ANTARA KEMAMPUAN BERPIKIR KREATIF DENGAN KETERAMPILAN MENULIS TEKS NARASI SISWA SD - Inayatul Ummah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2021)
Writing is often associated with a child's creativity. In this study, creativity was assessed using TCT-DP (The Test for Creative Thinking-Drawing Production) where students were asked to continue drawing the available patterns. This study aims to determine whether there is a relationship between students who are able to continue drawing patterns by writing narrative text well. This research was conducted in one of the SDN Citangkil District with a population of 2 classes totaling 88 students. The method used in this research is correlational descriptive. In this study, data from the creative thinking test uses 11 out of 14 criteria, namely: continuations, completion, new elements, the connection made with a line, the connection made to produce a theme, boundary-breaking that is fragment dependent, boundary-breaking that is fragment independent. , perspective, humor, and affectivity, unconventionally, and speed. These criteria are translated through scores of 1-3. The results showed that there was a relationship between students who had the ability to think creatively and write good narrative texts.